Describing the design thinking and extreme programming activities during a technology innovation academic workshop - Ivonei Freitas da Silva (Innovation & Management Review, 2020)
Purpose - This paper aims to describe the students' experience in adopting design thinking (DT) and extreme programming (XP) throughout a course of technology innovation workshop in a master of business administration (MBA) degree program. Design/methodology/approach This study analyzes data (performed process and achieved results) from the students' reports and the instructor's observations about three courses held in 2016, 2017 and 2018. In each course, there were students conducting activities to understand, develop, and validate the market, customer, user and prototype. Findings This paper identifies that the processes of DT and XP promote active and collaborative learning relationships. The adopted activities along with a mix of different backgrounds from the students can promote good insights to understand the user problem and build a technological solution with incremental innovation. Research limitations/implications This paper describes only a unique view from the instructor's knowledge; therefore, others might present different scenarios and results. Originality/value The paper contributes to the characterization of DT and XP activities when teaching technological innovation in a MBA.
Keywords: 650; Design thinking; Experience; Extreme programming; Master business administration